(untitled) (JED (Jurnal Etika Demokrasi), 2017)
The objective of this research is to improve the sociology learning outcomes of social interaction subjects with the method of discussion on the students of class X MA. Muhammadiyah Panaikang Kacamatan Bissappu Kabanta Bantaeng. This study included descriptive research designed through classroom action research, conducted in two cycles, each cycle was held as many as 4 times meeting with the number of students 34 people (13 men and 21 women). The instrument of this research is test and observation sheet. The data of the research are analyzed quantitatively and qualitatively. The results of this study showed: (1) Student learning achievement cycle I average 53.70 and increase in cycle II with an average of 82. Learning completeness in the first cycle of 58.82% and increased in cycle II to 57, 05% . Thus, the learning method can improve student’s sociology learning outcomes. (2) Discussion method can increase students’ activity in learning. Indicators of improvement can be observed based on observations from cycle I and to cycle II that undergo changes, the emergence of changes, motivation, enthusiasm, and the value of student learning students understand the material. Keywords: Learning Outcomes, Discussion Methods, Student Activity.